2021
DOI: 10.3390/polym13152473
|View full text |Cite
|
Sign up to set email alerts
|

The Amelogenin-Derived Peptide TVH-19 Promotes Dentinal Tubule Occlusion and Mineralization

Abstract: In this study, the amelogenin-derived peptide, TVH-19, which has been confirmed to promote mineralization, was evaluated to derive its potential to induce dentinal tubule occlusion. The binding capability of fluorescein isothiocyanate (FITC)-labeled TVH-19 to the demineralized dentin surface was analyzed by confocal laser scanning microscopy (CLSM). Additionally, the sealing function of the peptide was studied through the remineralization of demineralized dentin in vitro. The adsorption results showed that TVH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…So it was used to detect the surface of the caries lesions and remineralization areas of all specimens and to further explore the crystal phase structure of the peptide TRAP synthesized for regulating the remineralization of enamel caries lesions in this study. Previous studies have demonstrated that the product of an amelogenin-derived peptide applied for remineralization was HA ( Ruan et al, 2014 ; Peng et al, 2021 ). The N-terminal tyrosine segment of amelogenin was extracted from LRAP and synthesized into a biomimetic enamel matrix protein using non-amelogenin analogs.…”
Section: Discussionmentioning
confidence: 99%
“…So it was used to detect the surface of the caries lesions and remineralization areas of all specimens and to further explore the crystal phase structure of the peptide TRAP synthesized for regulating the remineralization of enamel caries lesions in this study. Previous studies have demonstrated that the product of an amelogenin-derived peptide applied for remineralization was HA ( Ruan et al, 2014 ; Peng et al, 2021 ). The N-terminal tyrosine segment of amelogenin was extracted from LRAP and synthesized into a biomimetic enamel matrix protein using non-amelogenin analogs.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the literature, the active peptide structure may affect the morphology of the generated and deposited HA crystals (Mannem et al, 2020). In the experiments conducted by Xiu Peng's group, the deposits formed after remineralization of active and inactive peptides showed two different crystalline forms, namely flakes and needles (Peng et al, 2021). Therefore, in future studies, we should focus on the new HA morphology after remineralization of each active peptide to identify the most suitable active peptide for restoring the original morphology and function of dentin.…”
Section: Active Peptidesmentioning
confidence: 99%
“…Our study presents innovative findings on our previously developed amelogenin-derived peptide, TVH-19, which has been demonstrated as a multifunctional peptide for antibacterial, enamel remineralization, and inflammation prevention in dental pulp. − However, the precise mechanisms underlying these effects remain elusive. In this study, we first investigated the underlying mechanism of TVH-19 multifaced effects on DPCX based on its structure–activity relationship.…”
Section: Introductionmentioning
confidence: 99%